CARACTERIZAÇÃO DE AMIDOS OBTIDOS DE DIFERENTES FEIJÕES E SUA APLICAÇÃO EM FILMES BIODEGRADÁVEIS - Figueroa, Amanda Mileo (2016)
Beans are starchy legumes (pulses) widely used for direct human consumption, because they provide carbohydrates, protein, fiber, and other nutrients. Among the most cultivated and consumed are the beans of Phaseolus and Vigna genera. Despite the high nutritional value, beans have anti-nutritional factors and their technological properties are altered upon how long they are stored. Due to loss of quality there may occur disposal of depreciated grains. To avoid waste, it is of great interest to research ways of reusing this raw material, for an example, for producing protein isolates, starch extraction, obtaining flour, among others. This present study aims to extract and purify starch of beans grown in Brazil, to characterize their properties and test their performance in the production of biodegradable films. The study was conducted with twelve kinds of commercial beans, considering physical characteristics and chemical composition. The extraction yield of the starches was different for the beans, and the purity was proved by the chemical composition. Starches have moisture contents ranging from 7.18 to 10.26 %, ash content, proteins and lipids lower than 0.1 % with amylose contents from 23.6 to 45.6 %. The starches were characterized in relation to the shape and size of their granules, and also by structural, technological and thermal properties. The average length of the granules was 26.8 micrometers. The starches showed maximum solubility index of 12.3 % at 90 °C, and the starch from Fradinho bean had the largest swelling power (32.1 %) for this temperature. Starch pastes presented clarity values close to 3 % transmittance, and syneresis around 50 %. The Fradinho bean starch showed the higher viscosities in viscoamylograph profile (RVA) and the highest enthalpy change in the DSC analysis. Both starches had three stages of thermal degradation and approximately 30 % crystallinity indexes (X-ray diffraction). The starches were used in preparing biodegradable films using glycerol as plasticizer. The films were analyzed for surface appearance, opacity, solubility, swelling power, permeability and mechanical properties. The biodegradable films had solubilities in water close to 20 %, higher swelling in solutions at pH 8.0, and low permeability to water vapor. The mechanical tests showed that the films prepared with starches of black beans and Rajado bean showed higher strengths, while the elongation ranged from 20 to 30 % for the different films. The results revealed that the beans and their starches have different characteristics; even if they belong to the same commercial group (black beans, for example) and that directly influence the quality of biodegradable films.